The Fishing Grounds and the Exploitation Status of Kawakawa (Euthynnus affinis) in Java Sea, Indonesia - Siti Mardlijah; Andina Ramadhani Putri Pane; Moh Fauzi; Helman Nur Yusuf; Heri Widiyastuti; Herlisman Herlisman; Achmad Zamroni; Tegoeh Noegroho; Hufiadi Hufiadi; Karsono Wagiyo (HAYATI Journal of Biosciences, 2022)
Kawakawa (Euthynnus affinis) is one of the highly favored mackerel tunas caught in Java Sea. The increase in demand due to local consumption and export eventually increases fishing that is proportional to the exploitation status. To maintain the fish resource, a scientific study should be carried out on the fishing grounds and the exploitation status of kawakawa. This study was carried out for 3 years, i.e. in March to October 2017, June to December 2018, and February to November 2019 at Pekalongan National Fishing Port in Pekalongan, Central Java, with 9,511 fish as the study objects. The data analysis was carried out by observing the fishing grounds using GPS and through interview. In addition, the exploitation status was analyzed using FISAT II application and ELEFAN program. The fishing grounds were mostly coastal waters with 15–55 cm sized kawakawa. The size of the first caught (Lc) of the kawakawa in this area ranged from 26.9 cm to 38.4 cm. The fish recruitment occurred all year long, peaking in Apr at 15.97% and Juli 13.62%.The fish natural mortality (M) was smaller than its fishing mortality (F), while its exploitation status was 0.66 (overfished), meaning that the current fishing efforts should be reduced by 32%. The other management efforts that can be carried out are among others conservation, keeping the fishing grounds outside the spawning grounds, and controlling the mesh size.